2020
DOI: 10.1001/jamaophthalmol.2020.1562
|View full text |Cite
|
Sign up to set email alerts
|

Association of Co-occurring Dementia and Self-reported Visual Impairment With Activity Limitations in Older Adults

Abstract: IMPORTANCEThe number of older adults with visual impairment (VI) and dementia is projected to increase in the US because of the aging of the population. Dementia and VI commonly co-occur and are each independently associated with disability. To care for an aging population, it may be important to characterize the association of coexisting dementia and self-reported VI on daily functioning. OBJECTIVE To evaluate the association of co-occurring dementia and self-reported VI on daily functioning. DESIGN, SETTING,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 22 publications
2
37
0
Order By: Relevance
“…An overlooked aspect of the caregiving paradigm is the role of co-occurring dementia and vision impairment on the caregiving needs of older adults, and the impact on those caring for them. While multimorbidity or the coexistence of any two or more health conditions is a risk factor for disability in older adults, and therefore can be argued to be associated with a magnified caregiving need profile, co-occurring vision and cognitive impairments have been shown to have an especially strong impact on functioning ( 9 , 10 ). Although vision and cognitive impairments affect various areas of daily functioning such as self-care, mobility, and household activities, activity limitations are not always analogous.…”
Section: Background and Objectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…An overlooked aspect of the caregiving paradigm is the role of co-occurring dementia and vision impairment on the caregiving needs of older adults, and the impact on those caring for them. While multimorbidity or the coexistence of any two or more health conditions is a risk factor for disability in older adults, and therefore can be argued to be associated with a magnified caregiving need profile, co-occurring vision and cognitive impairments have been shown to have an especially strong impact on functioning ( 9 , 10 ). Although vision and cognitive impairments affect various areas of daily functioning such as self-care, mobility, and household activities, activity limitations are not always analogous.…”
Section: Background and Objectivesmentioning
confidence: 99%
“…Although vision and cognitive impairments affect various areas of daily functioning such as self-care, mobility, and household activities, activity limitations are not always analogous. For example, mobility limitations are particularly relevant to adults with vision impairment while an impact on activities of daily living (ADLs) is more pertinent to cognitive impairment ( 9 , 10 ).…”
Section: Background and Objectivesmentioning
confidence: 99%
“…Whitson et al’s study suggested that people with vision impairment had greater odds of mobility disability [ 19 ]. Patel et al’s study also suggested that those with visual impairment would have lower mobility activities compared to those without [ 20 ]. However, both authors acknowledged that self-reported data were the limitation of their studies [ 19 , 20 ], particularly in the dementia group [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patel et al’s study also suggested that those with visual impairment would have lower mobility activities compared to those without [ 20 ]. However, both authors acknowledged that self-reported data were the limitation of their studies [ 19 , 20 ], particularly in the dementia group [ 20 ]. In contrast, we chose to gain disability data on an objective basis, and 84% of our patients with IRD (383 of 456) were officially in the decreased “disability status”, with an average of 54.17% loss of working disability being disclosed.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of sensory impairments on various developmental outcomes has been well documented. Self-reported vision impairment, which affects approximately 9% of adults age 65 and older in the United States (Patel et al, 2020), and self-reported hearing impairment, which affects 31% of those ages 60 to 69 and 63.1% of those age 70 and older (Goman & Lin, 2016), have a negative impact on many domains of health, functioning, and quality of life (Bainbridge & Wallhagen, 2014; Swenor et al, 2019; Teutsch et al, 2016). These challenges are compounded in the case of dual sensory impairment, which is present in up to 11% of adults age 60 and older (Correia et al, 2016; Saunders & Echt, 2007; Schneider et al, 2011; Swenor et al, 2013).…”
Section: Background and Objectivesmentioning
confidence: 99%